TRANSFORMASI PEMBELAJARAN BERBASIS DIGITAL MELALUI PEMANFAATAN INTERACTIVE FLAT PANEL (IFP) DI SMPN 3 GRATI SATU ATAP - Amilatun Nasiba; Ayu Maya Damayanti; Yuniar Mujiwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Transforming learning methods through technology is a crucial step toward enhancing educational quality in the era of Industry 4.0 and Society 5.0. One practical application is the use of Interactive Flat Panels (IFPs) as interactive learning tools that foster innovative, collaborative, and learner-centered educational processes. This study aims to explain the implementation of digital-based learning transformation via IFPs at SMPN 3 Grati Satu Atap, identify the factors facilitating or hindering this implementation, and analyze its impact on the learning process. A qualitative approach with a descriptive method was employed. Research subjects—comprising the principal, teachers, and students—were selected using purposive sampling. Data were collected through observation, in-depth interviews, and document analysis, then processed using an interactive analysis model involving data reduction, data presentation, and conclusion drawing. Data validity was verified through source and method triangulation. The findings indicate that IFP usage enhances learning effectiveness by making material presentations more engaging, interactive, and comprehensible. Teachers can more easily integrate diverse digital learning materials, while students demonstrate increased participation, enthusiasm, and critical thinking skills. Facilitating factors include adequate facilities, supportive school policies, and improved teacher digital literacy. Challenges include the limited technological proficiency of some teachers and a reliance on stable internet connectivity. The study demonstrates that the Interactive Flat Panel serves as an effective innovation in supporting the shift toward digital-based learning at SMPN 3 Grati. Furthermore, it highlights that learning quality can be enhanced through the continuous improvement of teacher competence and the ongoing development of technological infrastructure.